Single‐ and Multiple‐Dose Pharmacokinetics of Once‐Daily Formulations of Raltegravir. Issue 2 (17th April 2017) - Krishna, Rajesh; Rizk, Matthew L.; Larson, Patrick; Schulz, Valerie; Kesisoglou, Filippos; Pop, Radu
Abstract: A new once‐daily formulation of raltegravir, an integrase strand transfer inhibitor indicated in combination with other antiretroviral drugs for the treatment of human immunodeficiency virus–1 infection, is under development. Single‐dose and steady‐state pharmacokinetics of 1200 mg for 2 formulations of raltegravir were characterized in 2 open‐label phase 1 studies in healthy male and female subjects aged 18 to 55 years. The new raltegravir 600‐mg formulation had a higher relative bioavailability compared with the 400‐mg tablets. Once absorbed, both 3 × 400‐mg and 2 × 600‐mg dosage forms of raltegravir exhibited similar systemic pharmacokinetics; in dictating bioavailability, differences were from increased absorption that was the result of improved in vivo disintegration/dissolution. Food had a smaller effect on the pharmacokinetics of raltegravir when given as 2 × 600‐mg formulation (42% vs 73% decrease in AUC0–last ). Steady state was generally reached in 2 days, with little to no accumulation with multiple‐dose administration. Raltegravir 1200 mg was found to exhibit pharmacokinetic properties amenable for once‐daily dosing and was generally well tolerated in healthy subjects after single and multiple doses. The new formulation improved the bioavailability of this Biopharmaceutics Classification System class II compound.